Penguatan Manajemen Mendorong Kemandirian Kelembagaan Pengelolaan Irigasi Pasang Surut di Kalimantan Selatan - Rina D, Yanti; Panggabean, Elias Wijaya (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2014)
Tidal irrigation management at the tertiary level is facing constraints such as low participation of farmers and institutional role of Water Users Asociation (WUA) which is considered not optimal. WUA empowerment through strengthening of management is one of the efforts to promote self-governance of WUA. This study aims to measure the level of self-governance of the WUA groups through strengthening program management in tidal wetlands. Research was conducted from January to December 2012 using a qualitative approach by survey, in-depth interviews and participatory observation techniques to collect data. The sample group is WUA of Sri Rezeki at Karang Buah Village and WUA of Bina Usaha at Karang Dukuh (as a comparison), in Barito Kuala. Strengthening the management was conducted by applying management functions such as planning, organizing, implementing and controlling the organization of WUA. The results showed that strengthening the group management of WUA of Sri Rezeki generated: self-governance group with medium category, leadership with high category, management of group dynamics with high category, group effectiveness with high category and profitable farming for farmers.